Cell type-specific function of TRAF2 and TRAF3 in regulating type I IFN induction - Xiaoping Xie (Cell & Bioscience, 2019)
Abstract Background TRAF3 is known as a central mediator of type I interferon (IFN) induction by various pattern recognition receptors, but the in vivo function of TRAF3 in host defense against viral infection is poorly defined due to the lack of a viable mouse model. Results Here we show that mice carrying conditional deletion of TRAF3 in myeloid cells or dendritic cells do not have a significant defect in host defense against vesicular stomatitis virus (VSV) infection. However, whole-body inducible deletion of TRAF3 renders mice more sensitive to VSV infection. Consistently, TRAF3 was essential for type I IFN induction in mouse embryonic fibroblasts (MEFs) but not in macrophages. In dendritic cells, TRAF3 was required for type I IFN induction by TLR ligands but not by viruses. We further show that the IFN-regulating function is not unique to TRAF3, since TRAF2 is an essential mediator of type I IFN induction in several cell types, including macrophages, DCs, and MEFs. Conclusions These findings suggest that both TRAF2 and TRAF3 play a crucial role in type I IFN induction, but their functions are cell type- and stimulus-specific.